Race and Sex Differences in Intelligence and Personality: A Tribute to Richard Lynn at Eighty - Nyborg, Helmuth (2013)
This special issue commemorates Richard Lynn's work on individual differences on his eighty-second birthday, which took place on the twentieth of February, 2012. Richard Lynn has a long association with Personality and Individual Differences. This special issue consists of critical evaluations of Richard Lynn's work on national and racial differences in intelligence and personality, the effects of national IQs and economic development and a number of sociological, demographic and epidemiological phenomena, the Lynn-Flynn effect, sex differences in intelligence and specific abilities, eugenics and dysgenics, and the intelligence of the Jews.